فاعلية برنامج تدريبي مقترح قائم على التدريس التبادلي في تنمية التفكير الناقد والقدرة على حل المشكلات لدى معلمي الرياضيات بالمرحلة الإعدادية - عويضة، السيد عبدالعزيز محمد (جامعة سوهاج - كلية التربية, 2020)
هدف البحث الحالي إلى بناء برنامج تدريبي مقترح قائم على التدريس التبادلي لمعلمي الرياضيات بالمرحلة الإعدادية، وقياس فاعليته في تنمية قدرتهم على التفكير الناقد في الرياضيات وحل المشكلات الرياضية، وكذلك تحديد العلاقة بين قدرة المعلمين على التفكير الناقد في الرياضيات وقدرتهم على حل المشكلات الرياضية، ولذا قام الباحث ببناء البرنامج التدريبي المقترح، وبناء اختبار التفكير الناقد في الرياضيات، واختبار حل المشكلات الرياضية، وقام باختيار عينة عشوائية مكونة من 69 معلما ومعلمة للرياضيات بالمرحلة الإعدادية (36 تجريبية، 33 ضابطة)، وقام بتطبيق الاختبارات قبليا على المجموعتين التجريبية والضابطة، ثم تدربت المجموعة التجريبية باستخدام البرنامج التدريبي المقترح، وبعد الانتهاء من التدريب، تم تطبيق الاختبارات على المجموعتين التجريبية والضابطة، وبعد الحصول على البيانات ومعالجتها إحصائيا، توصل البحث الحالي إلى مجموعة من النتائج من بينها: - أداء معلمي الرياضيات بالمجموعة التجريبية في التفكير الناقد في الرياضيات وحل المشكلات الرياضية أفضل من أداء معلمي الرياضيات بالمجموعة الضابطة في الاختبار البعدي. - أداء معلمي الرياضيات بالمجموعة التجريبية في الاختبار البعدي لكل من التفكير الناقد في الرياضيات وحل المشكلات الرياضية أفضل من أدائهم في الاختبار القبلي. - فاعلية البرنامج التدريبي المقترح في تنمية قدرة معلمي الرياضيات بالمرحلة الإعدادية في كل من: معرفة الافتراضات، التفسير، الاستقراء، معالجة الأخطاء، التفكير الناقد بوجه عام - عدم فاعلية البرنامج التدريبي المقترح في تنمية قدرة معلمي الرياضيات بالمرحلة الإعدادية في كل من: تقييم الحجج والاستدلال. - عدم فاعلية البرنامج التدريبي المقترح في تنمية قدرة معلمي الرياضيات بالمرحلة الإعدادية في حل المشكلات الرياضية. - وجود علاقة ارتباطية موجبة ودالة إحصائيا بين قدرة معلمي الرياضيات بالمرحلة الإعدادية في حل المشكلات الرياضية وكل مهارة من مهارات التفكير الناقد في الرياضيات وهي: معرفة الافتراضات، التفسير، الاستقراء، تقييم الحجج، الاستدلال، معالجة الأخطاء، التفكير الناقد ككل. وقد أوصى البحث بضرورة إعداد مقرر خاص بالتفكير الناقد وحل المشكلات لطلاب شعبة الرياضيات بكليات التربية وتوظيف ذلك في تعليم الرياضيات في التعليم قبل الجامعي. وإعادة تنظيم محتوى منهج الرياضيات للصفوفK-12 ، بحيث يتضمن التفكير الناقد وحل المشكلات عبر هذه الصفوف.
The aim of the current research is to build a suggested training program based on the reciprocal teaching for preparatory school mathematical teachers, and measuring its effectiveness in developing their ability to a critical thinking in mathematics, and mathematical problem solving. It is aimed at determining the relation between teaches’ ability in a mathematical critical thinking and a mathematical problem solving as well. so the researcher has built the suggested training program and a mathematical critical thinking test and a mathematical problem solving test. The researcher selected random sample consisting of 69 preparatory school mathematical teachers (36 experimental, 33 control). Tests were applied on the experimental and control groups (pre-test), then the suggested training program was taught to the experimental group. After completing the training process, tests were applied on the two groups (post-test). Statistical analysis of the data has revealed a number of results: - The performance of the experimental group in mathematical critical thinking and a mathematical problem solving is better than the control group in the post-test. - The performance of the experimental group in mathematical critical thinking and a mathematical problem solving is better in the post-test than in the pre-test. - The effectiveness of the suggested training program in developing the preparatory school mathematical teachers in Know the assumptions, interpretation, induction, error handling and critical thinking as a whole. - The suggested training program wasn’t effective in developing the preparatory school mathematical teachers in evaluation of arguments and reasoning - The suggested training program wasn’t effective in developing the ability of the preparatory school mathematical teachers in mathematical problem solving. - There is a positive and statistically significant correlation between the ability of the preparatory school mathematical teachers in mathematical problem solving and every skill of the critical thinking; knowledge of assumptions, interpretation, induction, evaluation of arguments, reasoning, error handling and critical thinking as a whole. The research recommended the necessity of preparing a critical thinking and problem solving course for students of the mathematical department in the university of education, and using it in teaching mathematics in pre-university education and reorganizing the mathematics curriculum content for grades K-12 to include critical thinking and problem solving.
Keywords: الإستراتيجيات التعليمية -- طرق التدريس -- المناهج الدراسية -- معلمو الرياضيات -- التعليم الإعدادي